Hierarchy of the matrix Burgers equations and integrable reductions in the Davey-Stewartson system - Samoilenko, V. G.; Sidorenko, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate integrable reductions in the Davey-Stewartson model and introduce the hierarchy of the matrix Burgers equations. By using the method of nonlocal reductions in linear problems associated with the hierarchy of the Davey-Stewartson-II equations, we establish a nontrivial relation between these equations and a system of matrix Burgers equations. In an explicit form, we present reductions of the Davey-Stewartson-II model that admit linearization.